The Influence of Organiztional Communication Culture and Organizational Communication Climate on Professional Performance and Work Motivation of Teachers at MA Ura El-Mumtaz Education Foundation in Binjai City - M.Fahrur Rozy Stp; Iskandar Zulkarnain; Humaizi (Formosa Journal of Social Sciences (FJSS), 2024)
Communication within an organization plays a crucial role in determining the professionalism and work motivation of teachers. This study aims to examine the impact of organizational communication culture and organizational communication climate on the professional performance and work motivation of teachers at Maura El-Mumtaz Education Foundation. Using a quantitative approach, this research involved 36 teachers as respondents, selected through a total santpling method. Data were collected through a structured questionnaire designed to measure four main variables: organizational communication culture, organizational communication climate, professional performance, and work motivation. Data analysis was conducted using multiple linear regression techniques to determine the extent to which organizational communication culture and climate influence teachers' professional performance and work motivation. This study supports the Transitional Theory, which posits thatpositive changes in organizational communication culture and climate can enhance performance and work motivation. Additionally, the findings reinforce the Human Relations Theory, which emphasizes the importance of social interaction and effective communication in improvingjob satisfaction and productivity. The results of the study indicate that organizational communication culture has a positive and significant influence on teachers' professional performance